Telegram (copy)
029-0061-001 Copy of Telegram to "Direccion General de Abastecimientos, Ministerio de Hacienda y Economia", Barcelona, December 31, 1937. Text approved, Spanish Embassy, Commercial Attache, London, by Assistant Commercial Attache and Mr. William Gillies, in presence of Mr, G. T. Garratt. THE LABOUR PARTY AND CO OPERATIVE UNION OF GREAT BRITAIN INDICATE THE WISH THAT THE SHIPMENT OF SEVEN THOUSAND CASES OF CONDENSED MILK WHICH IS BEING EFFECTED BE DISTRIBUTED IN THE FOLLOWING MANNER: ONE HALF TO THE REFUGEES IN CATALONIA THROUGH THE ASSISTENCIA SOCIAL AND ONE HALF TO MADRID MUNICIPALITY AVOIDING ALL COMMERCIAL INTERVENTION AND SPECULATION STOP THEY WOULD LIKE AN EARLY REPORT FOR PUBLICATION FROM EACH AUTHORITY ACKNOWLEDGING RECEIPT OF THE MILK AND DESCRIBING HOW DISTRIBUTION HAS MET THE NEED OF THE VARIOUS CLASSES 30th December, 1937 292/946/29/61